If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -5z + -1y + -3z = 0 Reorder the terms: 10y + -1y + -5z + -3z = 0 Combine like terms: 10y + -1y = 9y 9y + -5z + -3z = 0 Combine like terms: -5z + -3z = -8z 9y + -8z = 0 Solving 9y + -8z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8z' to each side of the equation. 9y + -8z + 8z = 0 + 8z Combine like terms: -8z + 8z = 0 9y + 0 = 0 + 8z 9y = 0 + 8z Remove the zero: 9y = 8z Divide each side by '9'. y = 0.8888888889z Simplifying y = 0.8888888889z
| (3x-2)(5x+1)(x)= | | k-4/=3 | | 6y+33=-x+3 | | (5.8+4)-(7.2-9)= | | 2t+3=7 | | 30-4x=14-8x | | 1.04x+3.14=7.89 | | 17+90+x=18 | | 12-5r-2+4r= | | 4+6n=6+2n | | 2x-3+4x+11= | | 12x+6=2y-4 | | w=z^7-3z^6+13 | | 20(v+4)-4v=4(4v+1)-11 | | 7c+4b+3b+a+10c-5a= | | 3g+2h-7g+9g= | | 19w=13.5 | | f(x)=x^3-3x^2-8x+30 | | 6(x+5)=3(2x+1)+27 | | 13=-3+4r | | 8d-6e+9e-5d= | | 2x+16=x+21 | | 4x-9=-27 | | 2xy=4+x | | (1-6u+2x)(-8)= | | 11x+10=4x-25 | | 7v+2w-6v-3w= | | 4cosx*4cosx=0 | | 3.68-(6.72+2)= | | 6(4x-4)=3(8x+8) | | -y+5x=13 | | ln(x^3)=9 |